مدى الالتزام بتطبيق معايير المحاسبة الإسلامية في المعاملات المالية الإسلامية بالمصارف العامة العاملة في مدينة درنة (Economic studies journal, 2023)
The study aimed to find out the extent to which public commercial banks operating in the city of Derna adhere to the application of Islamic accounting standards in Islamic financial transactions. Moreover, knowing the extent to which there are differences in their application between the banks under study.In order to achieve the objectives of the study, the analytical descriptive approach was used, and data was collected through a questionnaire distributed to a number of employees in the banks under study, as it reached (152) respondents, which represents (91.5%) of the study population. Islamic accounting for the (One-Sample T Test) test, and to test the existence of statistically significant differences between the averages of the answers of the study sample in the banks’ application of Islamic accounting standards according to the bank, an Analysis of variance (ANOVA) test was conducted for the differences between the averages of two or more independent samples. At a significant level of 5% based on the SPSS software.The study reached a set of results, the most important of which are: that the commitment of the banks under study to apply Islamic accounting standards came in general with an average level of practice and at different rates. Among the averages of the answers of the sample of the study individuals regarding the availability of the requirements for applying Islamic standards in Islamic banks operating in the city of Derna, due to the type of bank; These differences showed that they are in favor of the Bank of the Islamic Republic, which means that it meets the requirements of applying Islamic accounting standards better than other banks. Among the most important recommendations of the study is the need to add courses related to Islamic economics and Islamic accounting and its application standards, and dealt with extensively in more than one stage of university studies, and the need for Islamic banks to raise the efficiency of their employees in order to apply Islamic accounting standards through holding courses and organizing specialized scientific conferences Calling experts to provide sufficient knowledge in the field of work and application of these standards.
Keywords: Islamic accounting standards; accounting and auditing institution for Islamic institutions; banks operating in the city of Derna